A Window into the Heterogeneity of Human Cerebrospinal Fluid Aβ Peptides. (23rd August 2011) - Ghidoni, Roberta; Paterlini, Anna; Albertini, Valentina; Stoppani, Elena; Binetti, Giuliano; Fuxe, Kjell; Benussi, Luisa; Agnati, Luigi F.
Abstract : The initiating event in Alzheimer's disease (AD) is an imbalance in the production and clearance of amyloid beta (A β ) peptides leading to the formation of neurotoxic brain A β assemblies. Cerebrospinal Fluid (CSF), which is a continuum of the brain, is an obvious source of markers reflecting central neuropathologic features of brain diseases. In this review, we provide an overview and update on our current understanding of the pathobiology of human CSF A β peptides. Specifically, we focused our attention on the heterogeneity of the CSF A β world discussing (1) basic research studies and what has been translated to clinical practice, (2) monomers and other soluble circulating A β assemblies, and (3) communication modes for A β peptides and their microenvironment targets. Finally, we suggest that A β peptides as well as other key signals in the central nervous system (CNS), mainly involved in learning and hence plasticity, may have a double-edged sword action on neuron survival and function.